2006
DOI: 10.1016/j.fgb.2005.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of expressed sequence tags from haustoria of the rust fungus Uromyces fabae

Abstract: Rust fungi are plant parasites which colonise host tissue with an intercellular mycelium that forms haustoria within living plant cells. To identify genes expressed during biotrophic growth, EST sequencing was performed with a haustorium-speciWc cDNA library from Uromyces fabae. One thousand seventeen ESTs were generated, which assembled into 530 contigs. Several of the most frequently represented sequences in the EST database were identical to the in planta induced genes (PIGs) identiWed previously (Hahn, M.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 37 publications
7
92
0
1
Order By: Relevance
“…Mould et al (2003) and Jakupovic et al (2006) have shown strong activation of POX during Uromyces vignae and Uromyces fabae infection of cowpea and broad bean, respectively. These authors showed activation of various isozymes of POX in infected wheat plants and concluded that the increase in POX activity was a consequence and not the determinant of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Mould et al (2003) and Jakupovic et al (2006) have shown strong activation of POX during Uromyces vignae and Uromyces fabae infection of cowpea and broad bean, respectively. These authors showed activation of various isozymes of POX in infected wheat plants and concluded that the increase in POX activity was a consequence and not the determinant of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rust haustoria were recently shown to be responsible for the uptake of carbohydrates (Voegele et al 2001). In addition, a large number of in planta-induced and haustorium-specific genes were identified to which no function could be assigned because of a lack of functional homologs in the databases (Jakupović et al 2005). The products of these genes are candidates for being involved in a major potential function of haustoria that has been under debate for decades, setting up and maintaining compatibility with the host plant (Bushnell and Rowell 1981;Voegele and Mendgen 2003).…”
mentioning
confidence: 99%
“…Their estimates based on DNA as a template were in the order of 20% fungal contribution to the total DNA sample. However, estimates by Jakupovic et al (2006) and our own quantifications (Voegele and Schmid, unpublished data) based on mRNA provided a considerably higher value, between 40% and 50% fungal contribution.…”
Section: Epidemiologymentioning
confidence: 59%
“…U. appendiculatus and P. graminis have been used in a number of cytological and physiological studies (Zhou et al 1991;Leonard and Szabo 2005). Today molecular analyses of rust fungi mainly focus on P. triticina (Thara et al 2003), M. lini (Catanzariti et al 2006), and U. fabae (Jakupovic et al 2006). Consequently, this chapter primarily focuses on work done using these organisms.…”
Section: A Brief History Of Rust Fungi and Rust Researchmentioning
confidence: 99%
See 1 more Smart Citation